Paraoxonase 1 as an important antiatherogenic agent - Krzewicka-Romaniuk, Ewa Lidia; Siedlecka, Dagna Agnieszka; Warpas, Anna; Wójcicka, Grażyna (Journal of Education, Health and Sport, 2019)
The inverse relationship between High Density Lipoproteins (HDL) level and risk of ischaemic heart disease was proved by many epidemiological studies. Although the main mechanism of antiatherogenic activity of HDL is a reverse transport of cholesterol from peripheral tissues to the liver, HDL additionally carries some antioxidative enzymes like Paraoxonase 1 (PON1) which protects LDL and HDL lipoproteins from oxidative modification. A lot of antiatherogenic activities of HDL depends on PON1 activity.